PEMBERDAYAAN KKN TEMATIK DALAM MENINGKATKAN SIKAP PEMAHAMAN REMAJA TERHADAP PENYALAHGUNAAN NARKOTIKA DAN PSIKOTROPIKA - Vivi Arfiani Siregar; Jamri Jamri; KMS Novyar Satriawan Fikri; Ali Azhar (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
Abuse of Narcotics and / or psychotropic substances can cause various adverse health effects and can even lead to death. But there is Narcotics and Psychotropic abuse that is rife in various countries including Indonesia. Whereas Regarding the Abuse of Narcotics and / or Psychotropics, it does not only come from adults but also from teenagers. There are also people who don't really understand what Narcotics, Psychotropics are, what bad effects can be caused by the abuse of Narcotics and / or Psychotropics and what legal sanctions they can face if they consume Narcotics and / or Psychotropics without rights or against the law. Such people are vulnerable to being targeted by drug dealers. Therefore, the implementation of this legal counseling work program is expected to increase public knowledge regarding the legal rules regarding Narcotics, Psychotropics and penalties for adolescents who commit crimes so that the community, especially teenagers, obey the applicable legal rules..